SISTEM INFORMASI MANAJEMEN PENDIDIKAN - Rahmah, Muftihatur; M. Taufik Akbar; Muh Rezqi Saputra; Sulkifli (As-Sulthan Journal of Education, 2025)
Educational Management Information Systems (EMIS) represent a systematic approach to managing information related to various educational aspects. This study aims to identify the definition, development, components, as well as planning, implementation activities, and security of EMIS. The research approach includes literature studies and conceptual analysis in the application of EMIS in various educational institutions. The results indicate that EMIS not only encompasses the management of academic and administrative data but also supports more effective and efficient decision-making. EMIS development involves strategic planning, user requirement gathering, and the design and implementation of technology-based systems. The main components of EMIS consist of hardware, software, human resources, and operational procedures that are optimally integrated. Furthermore, EMIS implementation planning requires systematic steps, including needs analysis, system design, testing, and continuous evaluation. Additionally, system security is a crucial aspect in protecting educational data from unauthorized access and damage. With proper planning and management, EMIS has the potential to enhance the quality of educational services and the effectiveness of management in educational institutions.